Molecular dissolved organic matter composition of porewater and water-extractable hot-water Soxhlet extracts - Melina Knoke; Philipp Böning; Thorsten Dittmar; Matthias Friebe; Eleonore Gründken; Jana Günther; Katrin Klaproth; Ina Ulber; Heike Simon; Michael Seidel (PANGAEA, 2025)
Molecular dissolved organic matter composition of porewater and water-extractable hot-water Soxhlet extracts. The dataset contains all molecular formulae found with Fourier-transform ion cyclotron resonance mass spectrometry including the respective isotope-free molecular formula, the hydrogen-to-carbon ratio (HC), oxygen-to-carbon ratio (OC), the aromatization index (AImod) and Double bond equivalent (DBE) and the relative intensity in each sample normalized to the total sum of intensities per sample. Samples were analysed with a Electrospray ionisation Fourier-transform ion cyclotron resonance mass spectrometry (ESI-FT-ICR-MS), Bruker Daltonik GmbH, Bremen, Germany connected to a 15 Tesla superconducting magnet (Bruker Biospin, Wissembourg, France), solariX XR, ICBM-OCEAN (https://rhea.icbm.uni-oldenburg.de/geomol/).
In: Knoke, M et al. (2025): Molecular composition of dissolved organic matter and biogeochemical parameters in porewater of Guaymas Basin (Gulf of California) deep subsurface sediments [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974052